Synergistic Inhibition of Mild Steel Corrosion in Hydrochloric Acid by Kecapi (Sandoricum koetjape ) Leaf Extract and Iodide Ions - Emriadi; Sari Wahyuni; Suryati (Departemen Kimia Universitas Andalas, 2026)
The corrosion inhibition performance of steel in hydrochloric acid solution using kecapi (Sandoricum koetjape (Burm.f.) Merr) leaf extract (KLE) and the synergistic effect of iodide ions was investigated using the weight loss method at temperatures ranging from 30 to 60 °C. The inhibition efficiency increased with increasing concentrations of both KLE and iodide ions, as well as with increasing temperature. A maximum inhibition efficiency of 86.61% was achieved at a KLE concentration of 6 g L⁻¹ in the absence of iodide ions, which further increased to 92.63% upon the addition of 0.5 g L⁻¹ iodide ions, indicating a pronounced synergistic effect. The adsorption behavior of KLE on the mild steel surface followed the Langmuir adsorption isotherm, suggesting monolayer adsorption. FTIR analysis revealed shifts in characteristic functional group bands, confirming interactions between extract constituents and the steel surface. SEM observations demonstrated significant improvement in surface morphology for mild steel specimens immersed in 1 N HCl containing KLE and iodide ions compared to the uninhibited solution. The synergistic effect between KLE and iodide ions was quantitatively evaluated using synergism parameters derived from inhibition efficiency values, confirming enhanced adsorption and corrosion protection.